2021
DOI: 10.3390/ijms22179431
|View full text |Cite
|
Sign up to set email alerts
|

Development of Effective Therapeutic Molecule from Natural Sources against Coronavirus Protease

Abstract: The SARS-CoV-2 main protease (Mpro) is one of the molecular targets for drug design. Effective vaccines have been identified as a long-term solution but the rate at which they are being administered is slow in several countries, and mutations of SARS-CoV-2 could render them less effective. Moreover, remdesivir seems to work only with some types of COVID-19 patients. Hence, the continuous investigation of new treatments for this disease is pivotal. This study investigated the inhibitory role of natural products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Glucobrassicin was reported to have inhibitory effects against SARS-CoV-2 protease [74]. Similarly, glucobrassicin from C. racemosa and P.boergesenii demonstrated the significant inhibition against RBD spike protein with the binding affinity of −6.8kcal/mol, even though it did not interact with the crucial residues that bonded with the ACE2 receptor (Table 2).…”
Section: Discussionmentioning
confidence: 95%
“…Glucobrassicin was reported to have inhibitory effects against SARS-CoV-2 protease [74]. Similarly, glucobrassicin from C. racemosa and P.boergesenii demonstrated the significant inhibition against RBD spike protein with the binding affinity of −6.8kcal/mol, even though it did not interact with the crucial residues that bonded with the ACE2 receptor (Table 2).…”
Section: Discussionmentioning
confidence: 95%
“…The scientific community has been racing to develop improved, sensitive, specific, and rapid SARS-CoV-2 detection devices that could be used for PoCT either at home or in resource-limited settings [139]. The early and rapid identification of infected patients can interrupt the chain of viral transmission by facilitating the isolation of infected individuals and allow quick provision of treatment options [140][141][142][143]. Studies have attempted to design various effective molecules against SARS-CoV-2 but the incidence of new variants and patient mortality will continue to increase without early and effective diagnosis [141][142][143].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the single-structure molecular mechanics-generalized Born surface area (MM/GBSA) rescoring method showed that quercetin-3- O -neohesperidoside (−87.60 kcal/mol) and myricetin 3- O -rutinoside (−87.50 kcal/mol) are more energetically favored than N3 (−80.88 kcal/mol), whereas myricitrin (MOR) is significantly less favored (−49.22 kcal/mol). 169…”
Section: Myricetin and Mpro Bindingmentioning
confidence: 99%